Relationships of adiponectin to regional adiposity, insulin sensitivity, serum lipids, and inflammatory markers in sedentary and endurance-trained Japanese young women - Guan, Yaxin; Zuo, Fan; Zhao, Juan; Nian, Xin; Shi, Li; Xu, Yushan; Huang, Jingshan; Kazumi, Tsutomu; Wu, Bin (Frontiers in Endocrinology, 2023)
The aim of this study is to compare the differences of circulating adiponectin levels and their relationships to regional adiposity, insulin resistance, serum lipid and inflammatory factors in young healthy Japanese women with different physical activity status. Adipokines (adiponectin and leptin), full serum lipid, inflammatory factors (WBC,CRP,TNF-α,PAI-1) were measured in 101 sedentary and 100 endurance-trained healthy Japanese women (age 18-23 yr). Insulin sensitivity was accessed by quantitative insulin-sensitivity check index (QUICKI). Regional adiposity [trunk fat mass（TFM）, lower-body fat mass（LFM）and arm fat mass（AFM）] was evaluated by DXA method. There was no significant difference between sedentary and trained women regarding adiponectin levels. LFM to TFM ratio and HDL-C were the strongest positive determinants for adiponectin in both groups. Triglyceride in sedentary women and PAI-1 in trained women, were closely and negatively associated with adiponectin. QUICKI was higher in trained than sedentary women. However, no significant correlation between adiponectin and insulin sensitivity was observed in both groups. Furthermore, LFM was associated with a favorable lipid profile against CVD in the whole study cohort and this association became insignificant when adiponectin was taken into account. These findings suggest adiponectin is primary associated with regional adiposity and HDL-C regardless of insulin sensitivity and physical activity status in young healthy women. Its lipid-modulating and anti-inflammatory effects are likely different in women with different physical activity status. LFM is correlated with a favorable lipid profile against CVD and adiponectin is likely involved in this association.